2007
DOI: 10.4049/jimmunol.179.4.2089
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptor Molecule CIN85 Regulates Syk Tyrosine Kinase Level by Activating the Ubiquitin-Proteasome Degradation Pathway

Abstract: Triggering of mast cells and basophils by IgE and Ag initiates a cascade of biochemical events that lead to cell degranulation and the release of allergic mediators. Receptor aggregation also induces a series of biochemical events capable of limiting FcεRI-triggered signals and functional responses. Relevant to this, we have recently demonstrated that Cbl-interacting 85-kDa protein (CIN85), a multiadaptor protein mainly involved in the process of endocytosis and vesicle trafficking, regulates the Ag-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 51 publications
3
24
0
Order By: Relevance
“…While a time-dependent decrease of Syk expression (∼50%) was observed in line with previous reported susceptibility of Syk to proteolysis [17,31,32], Hrs expression remained substantially stable until 8 h after FcεRI engagement, supporting the notion that Hrs modifications do not act as a degradation signal on mast cells. All together, our findings indicate that Syk/Cbl-induced Hrs modifications, without affecting protein stability, might impact on the ability of Hrs to function as endocytic adapter.…”
Section: Phosphorylation and Monoubiquitination Of Hrs Control Its Mesupporting
confidence: 73%
“…While a time-dependent decrease of Syk expression (∼50%) was observed in line with previous reported susceptibility of Syk to proteolysis [17,31,32], Hrs expression remained substantially stable until 8 h after FcεRI engagement, supporting the notion that Hrs modifications do not act as a degradation signal on mast cells. All together, our findings indicate that Syk/Cbl-induced Hrs modifications, without affecting protein stability, might impact on the ability of Hrs to function as endocytic adapter.…”
Section: Phosphorylation and Monoubiquitination Of Hrs Control Its Mesupporting
confidence: 73%
“…Several models have previously reported that retarding endocytosis of IgE/FcεRI complexes - through deletion of RabGEF1/Rabex-5, a guanosine nucleotide exchange factor (50), or by using cytochalasin D or latrunculin to block actin polymerization (39, 51) - resulted in elevated FcεRI signaling and production of specific cytokines by MCs. Similarly, accelerating the sorting of IgE/FcεRI complexes into early endosome/lysosomes by overexpression of CIN85, a molecule that regulates IgE/FcεRI endocytosis, resulted in attenuated FcεRI signaling (22,52). These prior studies, together with our current findings, highlight the largely overlooked role of MC endocytic circuitry and the intracellular location of these activities in regulating duration of mediator responses to allergens.…”
Section: Discussionmentioning
confidence: 48%
“…As previously mentioned, it is becoming evident that Cbl proteins play a critical role in the function of CIN85 in immune cells. [20][21][22] In addition, BCR-induced association of CIN85 with c-Cbl was recently shown even in mouse B cells. 44 We thus find that in human B cells, CIN85 negatively regulates BCR signaling via a Cbl-dependent mechanism.…”
Section: Discussionmentioning
confidence: 94%
“…20 In addition, it regulates Fc⑀RI signaling via Cbl-mediated regulation of Syk expression in RBL-2H3 cells. 21 A recent study showed that CIN85 modulates c-Cbl-mediated down-regulation of Fc␥RIIa in human neutrophils. 22 It is thus of interest to determine whether CIN85 regulates the signaling pathways of other multimeric immune receptors, such as the T-and B-cell receptors.…”
Section: Introductionmentioning
confidence: 99%